Ferroelectric and semiconductor film gas sensors - Tan, Ooi Kiang. (2008)
The field of research and development work on chemical gas sensors has been growing in the last few decades in view of the increasing awareness and concern for the environmental pollution. Currently, there are categorically five main directions in these works. They are the basic understanding for the sensing mechanism and principles; the search for new and improved materials for the sensing layer; the application of new material processing technology and techniques to prepare the material; the formulation of new physical chemistry concepts in relation with the microstructure of the sensor; and the improvement of characterization techniques to observe the microstructure and electrical behavior. For this Thesis work, two broad approaches are taken via the application of new sensing material and the material processing technology routes.